Symptomatic HIV CNS viral escape among patients on effective cART. (July 2019) - Manesh, Abi; Barnabas, Rohit; Mani, Sunithi; Karthik, Rajiv; Abraham, O.C.; Chacko, Geeta; Kannangai, Rajesh; Varghese, George M.
Highlights: Symptomatic HIV CNS viral escape presents as a global cerebral syndrome in treatment experienced patients. Atazanavir and Tenofovir may be associated with CNS viral escape due to poor CNS penetration. CNS viral escape produces a CD8 predominant inflammation in the CNS. Appropriate change of cART improves symptoms in most patients. Abstract: Objective: The clinical syndrome in symptomatic HIV associated CNS viral escape is poorly defined. We attempted to describe the clinical syndrome, laboratory profile, radiological features and outcomes of HIV infected patients with symptomatic central nervous system (CNS) viral escape in our study. Methods: This is a retrospective study were adult patients with HIV infection on cART admitted with a diagnosis of CD8 encephalitis or CNS viral escape in a large teaching hospital in South India was identified. Results: The mean age of the eleven patients included in the study was 37.5 years. Most patients had received almost a decade of antiretroviral treatment at diagnosis (mean: 11.18 years). All patients presented with global cerebral syndrome. Cognitive decline, tremors, and headaches were common manifestations. All patients had lymphocytic pleocytosis (mean cell count: 44.63 cells/ml; lymphocyte percentage: 94.81%) with elevated protein (mean: 125.36 mg/dl). All patients were on boosted protease inhibitors (81.8% on Atazanavir and 18.18% Lopinavir). All except one patient was on Tenofovir and lamivudine combination therapy. White matter changes and deep brain nuclei involvement were common. Most patients required a change of cART to regimens with better CNS penetration and suppression of the resistant virus in the plasma and improved. Conclusion: CNS viral escape should be considered as a differential among patients on Atazanavir presenting with non-focal cerebral syndrome and CSF lymphocytic pleocytosis.